Six-year distribution pattern of hepatitis C virus in Turkey: a multicentre study. Issue 2 (3rd March 2016) - Altindis, Mustafa; Dal, Tuba; Akyar, Isin; Karatuna, Onur; Gokahmetoglu, Selma; Ulger, Seda Tezcan; Kulah, Canan; Uzun, Berrin; Şener, Aslı Gamze; Ozdemir, Mehmet; Aydogan, Sibel; Kuskucu, Mert Ahmet; et al.
ABSTRACT: Hepatitis C infection is a public health problem. The aim of this retrospective study was to determine the distribution of hepatitis C virus (HCV) genotypes in seven regions of Turkey, by evaluating 7002 patients with chronic HCV in a six-year period. During the 2009–2014 period, serum/plasma samples from 7002 new consecutive HCV RNA positive patients were collected. The female patients were 3867 (55.2%). The genotype distribution of HCV patiens was evaluated by ages and years. Statistical analysis was performed by using the Mann–Whitney test and the χ 2 analysis. During the six-year period, genotype 1b was the most common genotype (67.7%) followed by untypeable genotype 1 (7.7%), genotype 4 (7.3%) and genotype 3 (6.7%). In 2014, genotype 3 was the second most common one (11.3%) and genotype 4 was the third most common one (9.8%). In the group with <25 years old patients, genotype 1b was most common (78.48%, 62/79) between the years of 2009 and 2011, whereas genotype 3 (34.8%, 86/247), between the years of 2012 and 2014. Genotype 1b was the most common in the groups between 26 and 35 years, 36 and 45 years, 46 and 55 years, 56 and 65 years. The rate of genotype 3 was increased from 4.78% to 10.06% and the rate of genotype 4 was increased from 1.3% to 3.84%, from 2009–2011 to 2012–2014. In recent years, genotypes 3 and 4 have gained importance. New therapeutic strategies and survey studies may be required for the modified HCV genotype pattern.